Right ventricular fibrosis in adults with uncorrected secundum atrial septal defect and pulmonary hypertension: a cardiovascular magnetic resonance study with late gadolinium enhancement, native T1 and extracellular volume - Ginting Munte, Fatwiadi Apulita; Elen, Elen; Lelya, Olfi; Rudiktyo, Estu; Prakoso, Radityo; Lilyasari, Oktavia (Frontiers in Cardiovascular Medicine, 2024)
Introduction Right ventricular (RV) fibrosis represents both adaptive and maladaptive responses to the overloaded RV condition. Its role in pulmonary hypertension (PH) associated with secundum atrial septal defect (ASD), which is the most common adult congenital heart disease (CHD), remains poorly understood. Methods We enrolled 65 participants aged ≥18 years old with uncorrected secundum ASD who had undergone clinically indicated right heart catheterization (RHC), divided into the non-PH group (n = 7), PH group (n = 42), and Eisenmenger syndrome (ES) group (n = 16). We conducted cardiovascular magnetic resonance (CMR) studies with late gadolinium enhancement (LGE) imaging, native T1 mapping, and extracellular volume (ECV) measurement to evaluate the extent and clinical correlates of RV fibrosis. Results LGE was present in 94% of the population and 86% of the non-PH group, mostly located at the right ventricular insertion point (RVIP) regions. LGE in the septal and inferior RV region was predominantly observed in the ES group compared to the other groups (p = 0.031 and p < 0.001, respectively). The mean LGE scores in the ES and PH groups were significantly higher than those in the non-PH group (3.38 ± 0.96 vs. 2.74 ± 1.04 vs. 1.57 ± 0.79; p = 0.001). The ES and PH groups had significantly higher degrees of interstitial RV fibrosis compared to those in the non-PH group, indicated by native T1 (1,199.9 ± 68.9 ms vs. 1,131.4 ± 47.8 ms vs. 1,105.4 ± 44.0 ms; p < 0.001) and ECV (43.6 ± 6.6% vs. 39.5 ± 4.9% vs. 39.4 ± 5.8%; p = 0.037). Additionally, native T1 significantly correlated with pulmonary vascular resistance (r = 0.708, p < 0.001), RV ejection fraction (r = −0.468, p < 0.001) and peripheral oxygen saturation (r = −0.410, p = 0.001). Conclusion In patients with uncorrected secundum ASD, RV fibrosis may occur before the development of PH and progressively intensify alongside the progression of PH severity. A higher degree of RV fibrosis, derived from CMR imaging, correlates with worse hemodynamics, RV dysfunction, and poorer clinical conditions.